تدني التحصيل الدراسي في مادة الرياضيات لدى طلبة الحلقة الثانية بمحافظة مسقط: دراسة من وجهه نظر المعلمين. The low academic achievement in the mathematics at the second cycle students in Muscat: teachers’ perspectives. - Alhadidi, Ibrahim Ali Mubarak; Al-Hidabi, Dawood Abdulmalek Yahya (2019)
This article discusses the reasons for the low acquisition of mathematics among the second seminar students at the province of Muscat in the Sultanate of Oman. The problem is the low achievement of mathematics, the focus of teachers on the Issues related to evaluation and neglect others, such as educational means, teaching methods, students economic and social conditions and others. Therefore, there was a lack of diagnosis of the main reasons for the students' low achievement by the teachers, this was clear to the researcher during his work as a teacher and supervisor, and during his discussion with officials in the supervision of education. The objectives of the study is to identify the causes that lead to low academic acquisition in mathematics among students of the second cycle of basic education from the teachers perspectives. The study sample consisted of )150( mathematics teachers for the second class, representing 50% of the study population. The questionnaires containing of (15) paragraph representing reasons for the low academic achievement by the students in mathematics. The findings revealed that the main reasons were: Lack of self-sense of the school drives the student not to interested in the study. Lack of desire to study. student bad behaviors that affect the acquisition level. Non-cooperation of parents with the school administration. The weak qualification of the student in the lower grades without being able of the basics of mathematics.